Treatment of Comorbid Migraine and Temporomandibular Disorders: A Factorial, Double-Blind, Randomized, Placebo-Controlled Study - Goncalves, Daniela A. G. [UNESP]; Camparis, Cinara M. [UNESP]; Speciali, Jose G.; Castanharo, Sabrina M. [UNESP]; Ujikawa, Liliana T.; Lipton, Richard B.; Bigal, Marcelo E. (Quintessence Publishing Co Inc, 2013)
Aims: To investigate the effectiveness of single and concomitant treatment of migraine and temporomandibular disorders (TMD) in women with the comorbidity. Methods: Eligible female patients met International Classification of Headache Disorders, second edition (ICHD-2) criteria for migraine with or without aura and the Research Diagnostic Criteria for myofascial TMD (Grade II or III). After a run-in period (30 days), women with both migraine and TMD were enrolled into a four-arm, double-blind, placebo-controlled, factorial study testing the separate and joint effects of a migraine treatment (propranolol 90 mg) and a TMD treatment (stabilization splint [SS]) in four groups of patients. The four treatment groups were propranolol and SS (n = 22); propranolol placebo and SS (n = 23); propranolol and non-occlusal splint (NOS) (n = 23); and propranolol placebo and NOS (n = 21). The primary endpoint for migraine was change in headache days from baseline to the third month, and the secondary endpoint was change in days with at least moderate headache in the same period. The TMD endpoints included pain threshold and mandibular vertical range of motion. Data were analyzed using analysis of variance (ANOVA, Dunn's post-hoc test) or Kruskal-Wallis test. Results: For the primary endpoint, in intention-to-treat (ITT) analyses (n = 94), propranolol and SS were associated with a nonsignificant reduction in the number of headache days, relative to all other groups. For per-protocol (PP) Completer analyses (n = 89), differences in the number of headache days reached significance (P < .05). The propranolol and SS group was significantly superior to the other groups on all other headache endpoints and in disability, in both ITT and PP analyses. No significant differences among groups were seen for the TMD parameters. Conclusion: In women with TMD and migraine, migraine significantly improved only when both conditions were treated. The best treatment choice for TMD pain in women with migraine is yet to be defined.
Keywords: clinical trial; migraine; occlusal splint; propranolol; temporomandibular disorders